The “Self-knowledge” program as the basis of the education system of the school - Kussainov, Askarbek; Kudysheva, Botagoz; Gulsara Kalieva, Arshagul Rysbaeva,; Duanabaeva, Bibi; Jakubakynov, Beibit; Jumanova, Gulnar (Opción, 2019)
The purpose of work is to show the features of the school education system via the methods of studying and systemic, complex and comparative analysis of various theoretical literature on educational issues. The results confirmed the effectiveness of the use of the program Self-Knowledge and showed that students’ autonomy increased. The study concludes that the main purpose of the education system is to form the system of personal values, the basis of students’ moral behavior, socially significant orientations that cause a person’s attitude to himself, to society, around the world, practical skills aimed at serving the community.